A formação do profissional de educação física e a perspectiva da saúde pública - Paulo, Camila Milan (2013)
The field work of physical education professional expansion that now considers their performance in health area and the implementation of Curriculum Guidelines for the graduate courses of Physical Education published in 2004 that also brings this perspective, so this study aimed to analyze the physical education professional formation of the public schools from São Paulo State under the health perspective. The methodological is based on a qualitative approach and the data collecting was achieved through document analysis of the pedagogical projects of the five schools analyzed in the study and semistructured interviews with the Course Coordinators of these schools. The dialogue between literature review and data research, built categories of analysis: a) A health focus: generally health content are still new in schools curricula, not having specifically targets to treat this perspective, b) Between reality and possibility: although the health content are not yet present in a systematic manner within the curriculum, two schools demonstrate innovative experiences that seek to break this situation, prioritizing comprehensive health care and multiprofessional work; c) Interdisciplinary content: schools showed a concern in breaking formats centric in unconnected contents, through the implementation of thematic curricula and synthesis disciplines, beyond experiences that value the multiprofessional work; d) Theory and practice in discussion: schools do not indicate clearly how the inseparability theory and practice is conceived within the curriculum of their courses, but merely to highlight the inseparability strategies (practice designed as a curriculum component, practical professional training and enrichment activities), proposed in National Curriculum Guidelines, yet not so cohesive and clear. Those questions indicate that changes should be thought either in the text of the National Curriculum Guidelines as the concept and elaboration of pedagogical projects from schools. Furthermore, the need for partnerships between university education and services, as well as the training of teachers for working in this area has appeared as emerging. The integrated curricula proposed, guided by the interprofessional education, interdisciplinary and problem-solving approach also emerged as a viable and effective alternative to changes in current reality.